Perception of San Marcos graduates on their pedagogical training within the framework of intercultural education - Sotomayor Torres, Yoshi (2021)
The main objective of the study is to analyze the perceptions of the graduates of the Faculty of Education in the National University of San Marcos regarding their pedagogical training in the framework of intercultural education. Among the specific objectives, the study investigates about graduates’ perceptions on the contents taught and the methodologies used by their professors, also about their perceptions on their internship and student coexistence in a markedly heterogeneous academic and social context. The approach of the study is qualitative, and the main data collection technique is the semi-structured in-depth interview. A total of 10 informants who completed their studies in 2018 were interviewed. The interviews were conducted between 2019 and February 2020 (pre-pandemic). Among the main results, it is found that both the curricular programming and the methodologies used by professors do not consider nor include the principles of intercultural pedagogy. Among the conclusions, in the Faculty of Education of San Marcos rules a monocultural curriculum that reproduces the hegemonic model, even though the main characteristic of the student population is their cultural and linguistic diversity.